Implementasi Pengembangan Pendidikan Wirausaha Pesantren Berbasis Kearifan Lokal di Kabupaten Jombang - Sucipto Sucipto (LP. Ma'arif Janggan Magetan, 2024)
Islamic boarding schools must be able to compete in the economic world so that they need entrepreneurship education to support them in the future, especially in Jombang as a student city. This study aims to reveal the implementation of education in Jombang Regency so far. The method is qualitative by conducting literature studies and data collection techniques in the form of interviews and documentation as well as analytical techniques in the form of reduction data, display data and drawing conclusions. The results show that the planning is carried out by establishing policies, rules and strategic designs of educational activities. Its organization by establishing the organizational structure of education and its tasks, the main and functions of each, the duration of training, the setting of targets and goals. Its implementation includes the determination of comprehensive and detailed activity achievement indicators so that the weaknesses and advantages of local wisdom products or related business units are known. Control and supervision are carried out routinely and actively accompanied by certain records in the field so that they can be used as evaluation material and can be followed up to become better.